Photoionization Impact on the Lightning Impulse Streamer Discharge of Rapeseed Insulating Oil: An Experimental Study - Yihua Qian; Qing Wang (Energies)
Photoionization is a significant factor influencing the morphology and propagation characteristics of streamers in insulating oil, yet research on the impact of photoionization on streamer branching is almost nonexistent. In this study, we employed an ultraviolet absorber to regulate the photoionization behavior of streamer discharges in rapeseed insulating oil. A quantitative assessment was conducted on the propagation morphology, length, and temperature distribution of positive and negative streamers. The results indicated that the streamer branches propagated in a dendritic manner. When photoionization was suppressed by the ultraviolet absorber, the streamer tended to generate more radially propagating branches, thereby shortening the axial stop length of the streamer branches by 1~3 mm. In addition, suppressing photoionization caused the maximum temperature to rise by approximately 74~220 K, generating more high-temperature hot spots within the streamer branches and promoting the formation of more radially propagating branches in the streamer. The analysis results demonstrated that suppressing photoionization weakened the axial electric field strength in the head region of the streamer branches, thereby inhibiting the electron avalanche behavior at the head of the streamer and thus reducing the rate of axial propagation of the streamer branches.